PERMAINAN TATA BALOK DALAM MENINGKATKAN KONSTRUKSI ANAK USIA DINI - Ayu Ariyanti; Buyung Surahman (Institut Madani Nusantara, 2023)
Play activities can invite children to explore, discover, and utilize objects around as a fun medium for children to develop aspects of their development. This opportunity through play should be given more to children because the benefits that children get greatly affect their development. Blocks provide opportunities for children to imagine, communicate, and work together. Children get the opportunity to represent ideas in form. building. Children through this construction game will learn solving problems, mathematics, science, and language.